Bean germplasm activities. Genetic variability from biotechnological techniques - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
During 1986, activities with Phaseolus in the biotechnology research unit focused on: developing tissue culture techniques for regeneration of bean plants using various organs and tissues; developing electrophoretic techniques for genotype identification; and monitoring research activities in aspects of bean biotechnology in other institutions, for the establishment of collaborative projects. Areas identified for this type of project are: (1) development of a tissue culture cycle in Phaseolus to allow regeneration of plants from nonorganized cell tissue cultures; (2) development of molecular markers in Phaseolus vulgaris using DNA restriction fragment length polymorphisms. The results obtained are included. (CIAT)